CONDIÇÕES DE TRABALHO, SAÚDE E QUALIDADE DE VIDA DOS CATADORES DE MATERIAIS RECICLÁVEIS, NO PERÍODO DE PANDEMIA DA COVID-19 - ALMEIDA, ANA PAULA (2022)
Waste pickers are part of a professional category that is often exposed to physical and psychosocial risks, and their working conditions in waste management are associated with losses in health and quality of life. Despite the existence of social policies that recognize the importance of the work of waste pickers, most of these workers still work in precarious and unhealthy conditions. The dangers originated from the emergence of new epidemics/pandemics widely disseminated, as is the case of COVID-19, add to these adversities in the lives of these professionals, since they faced, in the front line, an intense wave of biological risk. Given this context, the present work aimed to identify and diagnose the working conditions, health, and quality of life of the collectors of recyclable materials, during the pandemic period of COVID-19, in the city of Ponta Grossa-PR. For the development of the descriptive and exploratory research we used a sample composed of 83 participants linked to associations of collectors of recyclable materials. The collectors answered two questionnaires, the first constructed and subdivided into: Personal Data; Professional Profile; Occupational Health and Occupational Risks in the period of the COVID-19 pandemic, the second referring to the quality of life, from the application of the World Health Organization's quality of life instrument, "Whoqol-bref". Among the findings of the study, it was observed that the demographic profile of the waste picker tends to maintain the pattern already observed in the literature. The majority of the waste pickers who formed the sample were female (72,3%). The female gender also proved to have a greater number of children (66,3%). Approximately, 46,9% of the sample was between 18 and 35 years old, single (36,2%), with incomplete elementary school education (48,2%). The professional profile showed that most of the collectors (60,0%) did this work out of necessity or to supplement income and only 2% for professional fulfillment, although some recognize that their work is an extremely advantageous activity in environmental issues (29,0%). Regarding occupational health and occupational risks, during the pandemic period, it was identified that, although the waste pickers had developed protective strategies (93,9%) to avoid contamination by COVID-19, there was contact with potentially infectious waste (46,0%). The average overall quality of life on the Whoqol-bref assessment was 72 points (scale of zero to 100). The environment domain (63,5 points) and the social relations domain (71,0 points) had the lowest mean scores. The critical moment reveals the need for the development of emergency actions of preventive character to the collectors' health, in situations of epidemics/pandemics. From this diagnosis, it is possible to conclude that the pandemic of COVID-9 caused several changes in the lives of the waste pickers, some in the professional sphere and others related to emotional health. For this reason, longitudinal studies are suggested, at the end of the pandemic, to guide the development of strategies that can be adopted in other epidemic situations of wide dissemination, similar to those experienced in the period of COVID-19.